Combining environmental exposure and genetic effect measurements in health outcome assessment - Bonassi, S (Mutation research, 1999)
The presence of overwhelming difficulties in assessing the extent or even the presence of a causal association between modern environmental exposures and disease has promoted the use of more complex models in the design of human biomonitoring studies. The concatenation of environmental exposure, genetic effect and individual susceptibility is a key issue in the assessment of risks for populations exposed to environmental pollutants. The use of a biological event laying in the causal pathway from exposure to outcome as surrogate end-point of disease, can potentially anticipate clinical diagnosis, offering a number of possibilities for application of preventive measures. Numerous biomarkers are currently employed to study human populations exposed to environmental carcinogens, among these, the frequency of chromosomal aberration (CA) in peripheral blood lymphocytes has the most abundant literature linking a genetic effect with the occurrence of cancer. Findings from recent epidemiological studies which have followed-up a large group of healthy subjects screened for CAs have lent further support to the use of chromosomal breakage as a relevant biomarker of cancer risk. The applicability of surrogate end-points of cancer on an individual basis thus far seems to be limited to few examples. On the other hand, from a public health outlook, increases in the frequency of surrogate end-points are suggestive of an increased risk of cancer, and for validated biomarkers such as CAs intervention policies and actions in exposed populations showing increased frequency of these end-points should be always recommended.